1991
DOI: 10.1016/0014-5793(91)80721-e
|View full text |Cite
|
Sign up to set email alerts
|

Vasoconstrictor‐induced protein‐tyrosine phosphorylation in cultured vascular smooth muscle cells

Abstract: In cultured rat aortic smooth muscle cells, angiotensin II induced tyrosine phosphorylation of at least 9 proteins with molecular masses of 190, 117, 105.82,79,77,73,45 and 40 kDa in time-and dose-dependent manners. Other vasoconstrictors such as [Arglvasopressin, 5-hydroxytryptamine and norepinephrine induced the tyrosine phosphorylation of the same set of proteins as angiotensin II. The tyrosine phosphorylation of these proteins was mimicked by the protein kinase C-activating phorbol ester, phorbol 12 myr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
55
0

Year Published

1994
1994
2002
2002

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(59 citation statements)
references
References 26 publications
4
55
0
Order By: Relevance
“…This observation was supported by the similar potency of the tyrphostins against the contraction induced by calcium and by calcium plus GTP and NA in the x-toxin-permeabilized preparation. It may not be surprising that agonist independent contraction (K+-induced contraction of the intact arteries and calcium-induced contraction of the a-toxin permeabilized preparation) was inhibited by TKIs, since it has been shown in cultured vascular smooth muscle cells (Tsuda et al, 1991) that the calcium ionophore, ionomycin, can induce tyrosine phosphorylation. In fact, the tyrosine phosphorylation pattern induced by the ionophore was not dissimilar to that induced by vasoconstrictors including NA (Tsuda et al, 1991).…”
Section: Effect Of Tyrosine Kinase Inhibitors On Calcium-mediated Conmentioning
confidence: 99%
See 1 more Smart Citation
“…This observation was supported by the similar potency of the tyrphostins against the contraction induced by calcium and by calcium plus GTP and NA in the x-toxin-permeabilized preparation. It may not be surprising that agonist independent contraction (K+-induced contraction of the intact arteries and calcium-induced contraction of the a-toxin permeabilized preparation) was inhibited by TKIs, since it has been shown in cultured vascular smooth muscle cells (Tsuda et al, 1991) that the calcium ionophore, ionomycin, can induce tyrosine phosphorylation. In fact, the tyrosine phosphorylation pattern induced by the ionophore was not dissimilar to that induced by vasoconstrictors including NA (Tsuda et al, 1991).…”
Section: Effect Of Tyrosine Kinase Inhibitors On Calcium-mediated Conmentioning
confidence: 99%
“…(Bishop, 1987;Draetta et al, 1988), cellular interactions with the extracellular matrix (Schaller & Parsons, 1993) to force development (Berk et al, 1986;Yang et al, 1992). Conversely, classical constrictor agonists like angiotensin II, vasopressin and carbachol have been shown to activate smooth muscle tyrosine kinase and cause tyrosine phosphorylation (Tsuda et al, 1991), and have growth promoting effects. Thus, the tyrosine phosphorylation associated with the application of these hormones could be of importance for both the growth response and the contractile response of these cells.…”
mentioning
confidence: 99%
“…Evidence has been accumulating for some years now that tyrosine kinases are involved in receptor-mediated current inhibition, and in contraction and cell-signalling (Williams, 1989;Tsuda. et al, 1991;Wijetunge et al, 1992;Huang et al, 1993;Hollenberg, 1994;Felder, 1995;Wang & Salter, 1994;Moss et al, 1995;Wijetunge & Hughes, 1995;Hatakeyama et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…AII induces tyrosine phosphorylation of multiple proteins in cultured rat aortic vascular smooth muscle cells. 89,90 A lesser and more transient degree of tyrosine phosphorylation was seen in human aortic smooth muscle cells. 71 Focal adhesion kinase (p125FAK), 91 paxillin, 92,91 pp60src 93 and MAP kinases 71 (also known as ERK1 and ERK2) have all been identified as important targets in rat smooth muscle cells.…”
Section: Phospholipase C (Plc)mentioning
confidence: 95%
“…Inhibition of pp60src by anti-src antibodies inhibits AII-induced activation of PLC-␥, p21 ras and prevents proliferation in permeabilised rat aortic smooth muscle cells. 93 There is also evidence that a Ca 2+ -dependent tyrosine kinase may contribute to AII-induced tyrosine phosphorylation, possibly in conjunction with PKC, 89 since tyrosine phosphorylation of several proteins 97 including paxillin can be blocked by preventing the rise in [Ca 2+ ] i following AII. It has been suggested that this Ca 2+ -dependent tyrosine kinase could be related to another Ca 2+ -dependent tyrosine kinase, PYK2, previously described in neuronal cells.…”
Section: Phospholipase C (Plc)mentioning
confidence: 99%